Towards a more complete knowledge of the liverwort flora of Panama - Schäfer-Verwimp, Alfons (Phytotaxa, 2014)
One hundred and seven species, two subspecies and one variety of liverworts are newly reported from Panama including 27 species which were previously unknown from Central America. In total, 328 new province records are listed. The number of liverwort and hornwort species from Panama is now close to 470. Notes on the geographical distribution of the species are provided.